Simultaneous Therapeutic Plasma Exchange in Parallel with Cardiopulmonary Bypass for Prevention of HLA-Antibody Mediated Rejection in a Pediatric Double-Transplant Patient - Kazi, MD, Sofia; Carberry, RN, Deborah; Lagarde, RN, Ebben; Wu, MD, PhD, Ding Wen (North American Journal of Medicine and Science, 2012)
Therapeutic plasma exchange (TPE) has been used peri-operatively to prevent antibody-mediated rejection (AMR) in pre-sensitized solid organ transplant patients. Intraoperative TPE during cardiopulmonary bypass (CPB) has been reported in neonates receiving ABO-incompatible cardiac transplants, as well as in adults undergoing cardiac surgery. To our knowledge, intraoperative TPE in parallel with CPB (TPE-CPB) for prevention of human leukocyte antigen (HLA)-AMR has not been reported in pediatric cardiac transplantation. A 13 year old female with dilated cardiomyopathy, status post orthotopic cardiac transplant at 5 months of age, presented for cardiac re-transplantation due to end-stage heart failure and renal transplantation for end stage renal disease. Histocompatibility testing was weakly positive for antibodies to HLA-DQ6, with weakly positive donor crossmatch. In order to minimize ischemic time of the donor heart, TPE was performed while on CPB, immediately prior to cardiac transplantation. Apheresis machine access and return lines were connected via stopcocks to the CPB via proximal and distal ports, respectively, on the venous/low pressure side of the CPB circuit, before the CPB pump and oxygenator. The apheresis access line pressure alarm was set to 10 mm Hg less than the CPB pump pressure, to avoid pressure alarms and apheresis pump shutdown. The procedure was well tolerated, without complications. The subsequent renal transplant was uneventful. Post-operatively, no AMR was seen, and the patient continues to have good cardiac and renal function. Intraoperative TPE-CPB is feasible and safe, and may be considered for reduction of HLA antibody level immediately prior to cardiac transplantation in pediatric patients.